The Validity and Reliability of Electronic Students’ Worksheet Based on Discovery Learning on Thermochemical Topic - Soenarko, I Gede Karunia; Purwoko, Agus Abhi; Hadisaputra, Saprizal (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to evaluate an electronic student worksheets product based on discovery learning that valid and reliable on thermochemical topic. The development of electronic student worksheets-based on discovery learning follows the steps of the 4D development model, namely define, design, develop, disseminate. The feasibility test of the developed learning device was analyzed using a validation sheet. The assessment of the feasibility of the learning tools developed was carried out by three expert validators who are competent in the field of education at the University of Mataram. Criticisms and suggestions given by the validator are used as improvements to the developed electronic student worksheets. Data analysis was carried out using descriptive percentage techniques, Aiken's V index, and percentage of agreement. The validation results show that the developed electronic student worksheets component is included in the valid category with an average validity value of 0.79. The results of the agreement between validators showed that the developed electronic student worksheetshad a percentage of more than 75% which was included in the reliable category. Based on the results of the validation and reliability tests, the electronic student worksheets based on discovery learning developed can be concluded to be valid and reliable. A more complete and detailed explanation of the development of electronic student worksheets based on discovery learning and validation results is presented in this article.